Real-time determination of the activity of ATPase by use of a water-soluble polythiophene - Umit, Hakan Yildiz (2013)
This contribution introduces a fluorescence assay for real-time determination of the activity of p97/VCP, a 540-kDa homo-hexameric enzyme, belonging to the AAA-ATPase family. A fluorescent reporter “poly 1-(3-((4-methylthiophen-3-yl)oxy)propyl)quinuclidin-1-ium” (poly PTQ) is used to monitor the hydrolysis of ATP to ADP by p97/VCP. The proposed assay relies on the different strength of coordination of ATP and ADP to the polymer backbone. We used recovery of fluorescence intensity on addition of p97/VCP to a poly PTQ/ATP solution to determine the enzymatic activity. The kinetic data K m and V max were 0.30 mmol L−1 ATP and 0.134 nmol ATP min−1 μg−1 enzyme, respectively. The specificity of the assay was investigated by using an unhydrolyzable ATP analogue and sensitivity against p97 mutagenesis was further examined by detection of the activity of wild type and truncated p97/VCP. Our study demonstrates that determination of the real-time activity of p97/VCP is possible, because of the superior sensitivity and very fast optical response of poly PTQ.